Dynamics of religion in Southeast Asia: magic and modernity - Gottowik, Volker (Global Asia, 2014)
Spirit in and out of southeast Asia's modernity / Peter J. Bräunlein -- The social placing of religion and spirituality in Vietnam in the the context of Asian modernity / Michael Dickhardt -- Where the dead go to the market : market and ritual as social systems in upland southeast Asia / Guido Sprenger -- Modernity and spirit possession in Java : horse dance and its contested magic / Paul Christensen -- Hadhrami modern : recurrent dynamics as historical rhymes of Indonesia's reformist Islamic organization Al-Irsyad / Martin Slama -- Mubeng Beteng : a contested ritual of circumambulation in Yogyakarta / Susanne Rodemeier -- 'Muslim modernities' in Makassar and Yogykarta : negotiating 'the West' as a frame of reference / Melanie V. Nertz -- Cosmological battles : understanding susceptibility and resistance to transnational Islamic revivalism in Java / Thomas Reuter -- Modes of interreligious coexistence and civility in Maluku / Birgit Bräuchler -- Ethnicity and violence in Bali : and what Barong Landung says about it / Volker Gottowik -- Contested Moksa in Balinese Agama Hindu : Balinese death rituals between ancestor worship and modern Hinduism / Annette Hornbacher -- Good girls : Christianity, modernity and gendered morality in Tanah Karo, North Sumatra / Karin Klenke -- Bukit Kasih, the Hill of Love : multireligiosity for pleasure / Judith Schlehe.